An analysis method for nearshore laterally loaded rigid pile in cohesive soil. Issue 1 (2nd January 2018) - Ma, Lu; Wang, Yuke; Wang, Wei; Xu, Xiaoyang; Li, Songtao
ABSTRACT: Pile foundations for energy infrastructure, such as electric transmission towers, offshore platforms, or wind turbines, are usually rigid and close to the lateral response of rigid shafts. This paper presented an analysis method for the deflection of laterally loaded rigid pile in cohesive soil. The proposed method considers a broken-line variation of the ultimate horizontal soil resistance with depth. According to the elastic-perfectly plastic constitutive law and some calculation assumptions, there are four cases occurred with the increase of lateral load. For greater generality, the solutions have been given in dimensionless form. Comparing with numerical simulation and full-scale tests, the reasonability of the proposed method is demonstrated. The proposed method offers a simple alternative approach to the deflection of laterally loaded rigid pile in cohesive soil.